2019
DOI: 10.1080/00036846.2019.1676392
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fiscal consolidations on the composition of government spending

Abstract: Études et Documents is a working papers series. Working Papers are not refereed, they constitute research in progress. Responsibility for the contents and opinions expressed in the working papers rests solely with the authors. Comments and suggestions are welcome and should be addressed to the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…From a broad perspective, fiscal discipline is related to the ability of a government to maintain sustainable public finance. Several tools could enable to reach this objective namely fiscal consolidation programs (see Bamba et al [2020]) or fiscal rules. Irrespective of the complex issue of its measurement (see the next section), fiscal discipline in EMU is aimed to be ensured-as previously emphasized-by the supranational fiscal rules of the SGP and national fiscal rules.…”
Section: Fiscal Rules As a Policy To Promote Fiscal Discipline: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…From a broad perspective, fiscal discipline is related to the ability of a government to maintain sustainable public finance. Several tools could enable to reach this objective namely fiscal consolidation programs (see Bamba et al [2020]) or fiscal rules. Irrespective of the complex issue of its measurement (see the next section), fiscal discipline in EMU is aimed to be ensured-as previously emphasized-by the supranational fiscal rules of the SGP and national fiscal rules.…”
Section: Fiscal Rules As a Policy To Promote Fiscal Discipline: Theorymentioning
confidence: 99%
“…orCombes et al [2017]), or fiscal consolidations (see e.g Guichard et al [2007]. andBamba et al [2020]).…”
mentioning
confidence: 99%
“…Nevertheless, one under-appreciated angle is the effect of fiscal adjustments periods which remains a widespread subject. The related literature shows that few studies have analyzed how fiscal consolidation affects expenditure composition which have given little attention to social costs during fiscal consolidation episodes (Castro 2017;Bamba et al 2019). This has brought to the forefront the issue of transitional social costs during fiscal consolidation episodes.…”
Section: Introductionmentioning
confidence: 99%
“…First, to our knowledge, this paper is one of the first to empirically estimate the social expenditure effect of fiscal consolidations for emerging and middle-income countries. Our study attempts to specifically focus on the government expenditure and particularly social expenditure during fiscal consolidation episodes, a subject that has indeed received little attention in Castro (2017) and Bamba et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Second, some studies support that public investment is reduced during fiscal consolidations (see e.g. Alesina and Perotti, 1995), above the contraction of current spending (Bamba et al, 2019); in turn, fiscal consolidations are found to narrow spreads (Baldacci et al, 2011). Third, the composition of public spending better captures government's fiscal policy decisions, and particularly the existence of political budget cycles (see e.g.…”
Section: Introductionmentioning
confidence: 99%